PERANCANGAN GEDUNG PLANETARIUM DENGAN PENEKANAN NEO VERNAKULAR DI KOTA SAMARINDA - Setiyawan, Eko (LPPM Universitas 17 Agustus 1945 Samarinda, 2021)
The research objective of designing a planetarium building in Samarinda city, namely as one of the public facilities for recreation and education as well as the identity or icon of Samarinda City with a neo vernacular emphasis. The benefit of research for students is to improve their design skills in designing Planetarium Buildings using Architectural concepts. For the public, it is easy to get information about what products and facilities they offer. Research Methodology Primary data are direct interviews with relevant informants to get solid information. Observations, namely by making direct observations to the field. Secondary data search literature related to planetarium building design in books / internet. The results of the research determine the concept of building design and the achievement of planetarium building design with a neo vernacular emphasis in samarinda city.